The use of cooling and heating thermograms for monitoring of tallow, lard and chicken fat adulterations in canola oil - Marikkar, Mohammed Nazrim; Ghazali, H.M.; Che Man, Y.B.; Lai, O.M. (Elsevier, 2002)
The use of cooling and heating thermograms from differential scanning calorimetry (DSC) for monitoring the presence of genuine lard (GLD), beef tallow (BT), chicken fat (CF) as adulterants in canola oil has been investigated. Mixing of animal fats especially lard and tallow in any form in food products is a cause of concern for certain religions. Canola oil samples spiked separately with BT, GLD and CF in levels ranging from 1 to 20% (w/w) were analysed by DSC to obtain their cooling and heating profiles. The heating measurements showed that detection of GLD and BT adulterations could be possible based on characteristic differences of GLD and BT adulteration peaks appearing in the higher temperature region of heating thermograms while cooling measurements showed that BT adulteration could be determined by a distinct exothermic peak appearing in the higher temperature region of the cooling thermograms. The determination of GLD by cooling measurements could not be possible since the changes due to GLD and CF adulterations were very similar.